Study the structure of X(3872) from its lineshape - Hongge Xu; Ning Yu; Zuman Zhang (European Physical Journal C: Particles and Fields)
Abstract We fit the invariant mass distribution of $${X(3872)}→ J/{ψ }π ^+π ^-$$ X ( 3872 ) → J / ψ π + π - from LHCb using the propagator for S-wave near-threshold states in effective field theory. In this way, we can directly determine the Z which measures the projection of the bound state on the compact state in X(3872). Consequently, the structure of X(3872) can be elucidated. Moreover, the fitting result also can describe well the data for $${X(3872)}→ D^{0}\overline{D}^{0*}$$ X ( 3872 ) → D 0 D ¯ 0 ∗ from Belle experiment, which demonstrate the reliability of our fitting. The fitting indicates that Z is a non-vanishing value within error, which supports that X(3872) has a compact short-distant core.